TheUnipedia.Com: Fit or a Misfit? - Aamir Saeed; Mahnoor Amin; Shahnawaz Khan (International Journal of Experiential Learning & Case Studies, 2019)
This case is based on the entrepreneurial venture of MBA students from Mehran University of Engineering and Technology, named Ali Gohar (CEO) and Mubashsar Qureshi (CTO). Both studied at Cadet College and remembered the struggle they faced when they were looking for pretest preparations for the university admissions. That’s when they partnered to build the Unipedia, an easy way for struggling students to find quality aptitude test preparation at the low prices in comparison to coaching centres. This case is a brief about the online aptitude test preparation services in Pakistan. It will be a quick understanding of the industry dynamics and as to how the customer functions in this industry.